Multiscale electromagnetic SERS enhancement on self‐assembled micropatterned gold nanoparticle films. (1st June 2014) - Leordean, Cosmin; Potara, Monica; Boca‐Farcau, Sanda; Vulpoi, Adriana; Astilean, Simion; Farcau, Cosmin
<x xml:space="preserve">Abstract</x> In this work, we demonstrate a cascaded, multiplicative electromagnetic enhancement effect in surface‐enhanced Raman scattering (SERS) on periodically micropatterned films made of colloidal gold nanoparticles, prepared by a self‐assembly approach, without implying lithography procedures. The multiplicative enhancement effect is obtained by combining surface plasmon near‐field enhancement due to nanoscale features with far‐field photonic coupling by periodic microscale features. The effect is observed for both internal Raman reporters (molecules attached to the Au colloids before their assembly) and external Raman probes (molecules adsorbed on the samples after film assembly). The ability of the patterned films for far‐field light coupling is supported by reflectivity spectra, which present minima/maxima in the visible spectral range. Finite‐difference time‐domain computer simulations of the electric field distribution also support this interpretation. The fabricated dual‐scale SERS substrates exhibit a good spot‐to‐spot reproducibility and time stability, as proved by the SERS response over a time scale longer than 1 month. The experimental demonstration of this cascaded electromagnetic enhancement effect contributes to a better understanding of SERS and can affect future design of SERS substrates. Moreover, such dual‐scale colloidal films prepared by convective self‐assembly can be of general interest for the broader field of nanoparticle‐based devices. Copyright © 2014 John Wiley & Sons, Ltd.